Innovation, Information, and Financial Architecture - Tadesse, Solomon (Journal of Financial and Quantitative Analysis, 2006)
Abstract Does a financial system architecture anchored on banks perform better than one centered on markets in fostering technological innovations as engines of growth? In a panel of industrial sectors across a large cross section of countries, I find that while market-based systems have a general positive effect on innovations in all economic sectors, bank-based systems foster more rapid technological progress in more information-intensive industrial sectors, suggesting a heterogeneous impact of financial architecture. Thus, the relative performance of bank-based systems vis-à-vis market-based systems depends on the industrial structure of the economy.